Analisis Filogenetik Genus Alocasia - Azalia Sheehan Darupamenang; Beivy Kolondam; Song Nio Ai; Trina Tallei (Universitas Sam Ratulangi, 2022)
Alocasia (famili: Araceae) is a genus of plants with economic value because they can be eaten and some of them are known as decorative plants, such as Alocasia Jacklyn. The information about Alocasia Jacklyn is still very limited. This study aimed to identify and reconstruct phylogenetic trees of Alocasia Jacklyn using the DNA barcode of matK and rbcL genes. Analysis of varuations sequences of rbcL genes indicated of there was a difference of 4 – 7 nucleotides with the nearest relative but had a difference of 21 nucleotides with the farthest relative. The result of phylogenetic tree construction indicated there Alocasia Jacklyn is based on rbcL are siblings with Alocasia macrorrhizos in the position of phylogenetic tee, using matK indicated there Alocasia Jacklyn was closely related with Alocasia longiloba and using a combination of rbcL-matK genes indicated there Alocasia Jacklyn was siblings with Alocasia macrorrhizos and all of them included in the monophyletic group from the same genus of Alocasia because they’re from the same ancestry.